Colorectal cancer screening program implementation: biennial adherence and participation patterns - Priego-Parra, B.A.; Triana-Romero, A.; Inurreta-Vásquez, A.; Laffitte-García, H.; Violante-Hernández, G.A.; Jiménez-Rodríguez, S.S.; Martínez-Pérez, G.P.; Meixueiro-Daza, A.; Grube-Pagola, P.; Remes-Troche, J.M. (Revista de Gastroenterología de México (English Edition), 2024)
Adherence to colorectal cancer (CRC) screening is essential for the effectiveness of screening programs. Even though organized screening programs can improve the quality of the process and adherence, there are still challenges to overcome. The aim of the present study, in which we implemented a biennial organized screening program for CRC, was to describe adherence and participation patterns. A longitudinal, descriptive study was conducted, in which a team of trained patient navigators carried out interventions, with reminders via cellphone communication, to follow a cohort of 301 subjects eligible for CRC screening, utilizing a fecal immunochemical test (FIT). All the follow-up subjects received a FIT kit. A total of 747 cellphone calls were made and divided into three interventions. From the initial cohort, 126 subjects completed their biennial screening process through the FIT, indicating a consistent adherence rate of 41.8% to our program. The participation patterns were: 126 consistent participants (41.8%), 160 inconsistent participants (53.2%), and 15 participants that were never contacted (5%). In conclusion, our study underlines the importance of organized screening programs in the early detection of CRC. The implementation of follow-up interventions, through reminders and the training of patient navigators, can improve adherence, but there is a need for examining new strategies, to overcome barriers to communication via cellphone. La adherencia al tamizaje del cáncer colorrectal (CCR) es esencial para la efectividad de los programas de escrutinio. A pesar de que los programas de tamizaje organizado pueden mejorar la calidad del proceso y la adherencia, aún hay desafíos para lograrlo. En este estudio, implementamos un programa bienal de tamizaje organizado para CCR con el objetivo de describir la adherencia y los patrones de participación. Se realizó un estudio longitudinal y descriptivo en el que un equipo de navegadores de pacientes capacitados realizó intervenciones con recordatorios mediante llamadas telefónicas para dar seguimiento a una cohorte de 301 sujetos elegibles para el tamizaje de CCR mediante una prueba de inmunoquímica fecal (FIT). Todos los participantes que cumplieron con su seguimiento recibieron un Kit FIT. Se realizaron 747 llamadas telefónicas divididas en tres intervenciones. De la cohorte inicial, 126 sujetos completaron su proceso de tamizaje bienal mediante FIT, lo que indica una adherencia consistente del 41.8% a nuestro programa. Los patrones de participación fueron 126 participantes consistentes (41.8%), 160 inconsistentes (53.2%) y 15 nunca atendidos (5%). En conclusión, nuestro estudio resalta la importancia de los programas de tamizaje organizado en la detección temprana del cáncer colorrectal. La implementación de intervenciones de seguimiento mediante recordatorios y la capacitación de navegadores de pacientes, puede lograr mejoras en la adherencia, sin embargo, es necesario explorar nuevas estrategias para superar las barreras en la comunicación telefónica.